LEARNING PROBLEMS OF ISLAMIC EDUCATION AT SMA LB OF REJANG LEBONG - Idi Warsah (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
AbstractChildren with disabilities have the same rights in terms of education, both general and Islamic religious education. The present study aimed to investigate the main learning problems of Islamic education subject for students with disabilities. This study was conducted at SMA LB of Rejang Lebong. This study applied a descriptive qualitative approach. The Islamic education teacher at this school was engaged as the subject. The data were collected using interview and observation techniques. The data were further analyzed using an interactive model whose elements included data collection, data condensation, data display, and conclusion drawing. This study revealed that there were three main problems in Islamic education learning found at SMA LB of Rejang Lebong. These problems included a lack of teaching staffs (teachers), lack of parental supports, and lack of training provisions for the Islamic education teacher in an effort to help the teacher provide ideal teaching and learning processes for students with special needs. The findings of this study call for immediate solutions to be offered, especially by the school per se and Rejang Lebong’s local government.Keywords: Problems; Islamic education learning; Students with disabilities Abstrak Anak penyandang disabilitas memiliki hak yang sama dalam hal pendidikan, baik pendidikan umum maupun pendidikan agama Islam. Penelitian ini bertujuan untuk mengetahui permasalahan pokok pembelajaran pendidikan Islam bagi siswa disabilitas. Penelitian ini dilakukan di SMA LB Rejang Lebong. Penelitian ini menggunakan pendekatan kualitatif deskriptif. Guru mate pelajaran pendidikan agama Islam di sekolah ini dilibatkan sebagai subjek penelitian. Pengumpulan data dilakukan dengan menggunakan teknik wawancara dan observasi. Selanjutnya, analisis data menggunakan model interaktif yang elemen-elemennya meliputi pengumpulan data, kondensasi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini mengungkapkan bahwa terdapat tiga masalah pokok dalam pembelajaran pendidikan agama Islam di SMA LB Rejang Lebong. Permasalahan tersebut antara lain adalah kurangnya tenaga pengajar (guru), kurangnya dukungan orang tua, dan kurangnya bekal pelatihan bagi guru pendidikan Islam dalam upaya membantu guru untuk memberikan proses belajar mengajar yang ideal bagi siswa berkebutuhan khusus. Temuan studi ini mengundang agar segea ada solusi yang ditawarkan terutama dari sekolah itu sendiri dan pemerintah daerah Rejang Lebong.Kata Kunci: Masalah, Pembelajaran pendidikan agama Islam; Siswa disabilitas